Adaptive quadratic optimisation with application to kinematic control of redundant robot manipulators. Issue 4 (12th March 2023) - Zhang, Yinyan; Xiao, Gang; Li, Shuai
ABSTRACT: The primal-dual gradient dynamics is a broadly investigated approach for handling optimisation problems. In this paper, we provide an extension of such dynamics under the adaptive updating framework for solving equality-constrained quadratic programmes. We show that the performance of the proposed method is theoretically guaranteed and it has asymptotic convergence to the solution of the optimisation problem and the minimum inter-event time is non-trivial. A numerical example and an application show the effectiveness and advantages of the proposed method.